Variation in Lifestyle-Related Behavior Among Obese Indian Patients With Non-alcoholic Fatty Liver Disease - Arora, Charu; Malhotra, Anita; Ranjan, Piyush; Vikram, Naval K.; Dwivedi, S. N.; Singh, Namrata; Shalimar,; Singh, Vishwajeet (Frontiers in Nutrition, 2021)
Lifestyle modification is the mainstay of treatment in Non-Alcoholic Fatty Liver Disease (NAFLD). Published Indian data on the diet and lifestyle of Indian NAFLD patients is scarce. This study explored variation in lifestyle-related behaviour among obese patients with NAFLD. Ultrasonography (USG) diagnosed obese NAFLD patients (n=140) were assessed for dietary intake [one-day 24-hour recall, food-frequency questionnaire (FFQ)] and physical activity (PA) [Global Physical Activity Questionnaire (GPAQ)]. Diet quality score (0-30) and physical activity (PA) levels were used to study variation in lifestyle and assess the effect of lifestyle on the severity of NAFLD. Compared to the recommendation, calorie consumption was 25.2% higher in nearly half (53.6%) of the subjects and mean macronutrient intake was imbalanced (60.3% carbohydrates, 12.4% protein, 25.5% fats). Variation was seen in terms of diet quality – good (3%), moderate (54.3%), or poor (43.5%) and intensity of PA – low (37.1%), moderate (47.9%) or high (15%). No patient had a combination of high PA and good diet quality within all grades of NAFLD. Our study suggests wide variation in lifestyles of obese patients with NAFLD and need for a more flexible and individualized modification of their diet and PA.